Serum dipeptidyl peptidase-4 activity and progranulin level in polycystic ovary syndrome - Maryam Abolghasemi; Soleiman Mahjoub; Sedighe Esmaeilzadeh (Babol University of Medical Sciences, 2022)
Background: Evidence showed that abnormal alteration of adipokines level may perform a key role in polycystic ovary syndrome (PCOS) pathogenesis. Dipeptidyl peptidase-4 (DPP4) and progranulin (PGRN) are two novel adipokines related to insulin resistance (IR). Thus, we aimed to determine the serum DPP4 activity and PGRN level in PCOS patients with and without IR, and non-PCOS women. Methods: Ninety women were recruited in the present study including 60 PCOS patients (divided into two groups of 30 IR and 30 non-IR) and 30 non-PCOS women. Serum levels of insulin, fasting blood glucose, PGRN, and DPP4 activity were measured, and IR indices were calculated. Results: DPP4 activity was significantly higher in PCOS-IR and PCOS-NIR patients than non-PCOS women (p<0.001, P=0.011, respectively), whereas no significant variation was detected between two groups of PCOS subjects. There was no significant difference in the level of PGRN in the three groups of the present study. Conclusion: The present study suggests that increasing DPP4 activity may be associated with PCOS.